Pengenaan Pajak Pertambahan Nilai terhadap Obat - Sri Mulyani (Jurnal Acitya Ardana, 2022)
Value Added Tax (VAT) is an important for Indonesia. The imposition of VAT on medicine as BKP can increase the purchase price of the medicine. However, medicine is a very important and basic need for public health. So, it’s availability cannot be ignored. The purpose of this study is to review the government's policy on the imposition of VAT on medicine and identify the best treatment and the impact that can be caused by the imposition of VAT on medicine. The author uses a qualitative method with data retrived from a literature study on regulations about VAT on medicine delivery and uses data from interviews with several sources. The conclusion of this study is found that a difference in the imposition of VAT on pharmaceutical installations for medicine delivery, for outpatients are still subject to a 10% tariff, while inpatients are not subject to VAT because they are part of health services which are non taxable. The imposition of VAT on medicine has the potential to increase selling prices and reduce the level of access and utilization by the public. However, if VAT on medicine is abolished or reduced, there will be potential crimes by irresponsible parties.